2020
DOI: 10.4314/ejst.v13i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, relative abundance, and habitat association of avian species in Tara Gedam Monastery forest and adjacent habitats, Northwestern Ethiopia

Abstract:   Birds are important bio-indicators and provide various ecosystem services including pollination, dispersal, and pest control. However, they are threatened by habitat loss, fragmentation, and degradation. Study on species diversity, relative abundance, and habitat associations of avifauna were conducted in Tara Gedam Monastery forest patch and associated habitats from July 2016 to April 2017. Stratified random sampling approach was used to classify habitats and select sampling plots based on veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
4
2
1
Order By: Relevance
“…In this instance, the study site's relatively large natural forest habitat supports a higher number of species and more abundant species than other types of habitats. This coincides with the study result reported by [36,26] . They pointed out the high diversity of bird species in that natural forest is heterogonous in vegetation structure and possesses a more complex canopy capable of providing birds with sufficient food sources and nesting materials.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this instance, the study site's relatively large natural forest habitat supports a higher number of species and more abundant species than other types of habitats. This coincides with the study result reported by [36,26] . They pointed out the high diversity of bird species in that natural forest is heterogonous in vegetation structure and possesses a more complex canopy capable of providing birds with sufficient food sources and nesting materials.…”
Section: Discussionsupporting
confidence: 94%
“…During the wet season, birds shift from farmland habitat to natural forest crossing plantation forest habitat and vice versa during the dry season in search of food. This coincides with the study results reported by [36,41,42] who described that birds are naturally mobile and reside in habitats where foraging resources, nesting materials, and breeding necessities are periodically available. When comparing the potential effect of seasonality and resource availability in an ecological interaction context, [43] demonstrated that the daily activity of bird species is directly influenced by variability in forest microclimate but indirectly influenced by resources availability.…”
Section: Discussionsupporting
confidence: 92%
“…e riverine woodland habitat has the highest bird species diversity, richness, and evenness during the dry season, and this result is also in line with [26,33]. is is due to the occurrence of rich habitat diversity with both structure and species composition of plants in this habitat.…”
Section: Discussionsupporting
confidence: 67%
“…e survey was conducted along a series of point counting stations by counting the number of birds detected [26,27]. To avoid double counting, routes were spaced as adopted from [28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation